After the Trade Dispute: Is Indonesian Food Sovereignty Threatened? - Kadek Sarna; Nurhasan Ismail; Harry Supriyono (Faculty of law Udayana University, 2020)
The winning of New Zealand and the United States in a trade dispute with Indonesia regarding quantitative restrictions on the import of horticultural products, animals and animal products at the World Trade Organization (WTO) dispute panel assembly with case number DS (Dispute Settlement) 477 and 478, forces Indonesia to adjust its national policies with the existing rules in the 1994 GATT. This obviously becomes a concern for Indonesia's goal of realizing national food security and food sovereignty. This article aims to discuss how Indonesia's position in the case of DS 477 and DS 478 and how policy efforts in agriculture can be implemented so that Indonesia can withstand the development of international trade liberalization. This article is normative legal research that applies case and statutory approaches. It discusses the legal position of Indonesia when defending its reasons behind the restriction policies as well as analyses Indonesia’s opportunities to create food sovereignty and proposing legitimate policies after the cases decided. This article concludes that despite Indonesia was defeated in these cases, the opportunities for Indonesian agricultural products to be internationally marketed are still available and that bilateral arrangement would enable Indonesia to discuss the upcoming legitimate measures to be adopted. Reflecting on the results of WTO DS 477 and DS 478 cases, Indonesia should propose a Mutually Agreed Solution (MAS) and improving the provisions on horticulture imports and imports of animal products, carry out intensification and extensification policy, combat food cartels, and pay concern on the creation and implementation of various international trade regulations.